Analiza przestrzeni informacyjnej Biblioteki Uniwersytetu Gdańskiego - Kulczycka, Urszula (Biblioteka w chmurze czy chmury nad biblioteką, 2018)
The modern world is dominated by information, the importance of which is constantly growing. To say that members of the modern society are living in information`s environment is truism, but most important thing in the communication process is commitment of technology. This increases the importance of digital competence and increases the aspirations of society in respect of access to knowledge in a fast, easy and convenient way. Contemporary infospace, especially virtual, is more and more complex, dynamic and scattered. An example of such space mighty be online digital libraries, databases, and catalogs. This article discusses how the Library of the University of Gdańsk is now making an attempt to respond to or client`s needs.